Karakteristik dan Nilai-Nilai Kewirausahaan Selaku Pelaku Ekonomi di Era Sekarang - Azizah, Nur (CV. Pusdikra Mitra Jaya, 2025)
Entrepreneurship is the process of identifying, developing, and bringing a vision to life. This vision can be an innovative idea, an opportunity, or a way to improve at something. At the end of this process, there is a result in the creation of a new business formed under conditions of risk or uncertainty. Simply put, entrepreneurship can be defined as someone who has the courage to take risks to open a business in various opportunities. This research method uses qualitative research, namely research that describes in depth what has been obtained from others, both in the form of written words and verbally. This study also attempts to understand the research object according to the facts in the field without engineering/manipulating data. In this study, an empirical research method is applied that there are several superior characteristics of Minang ethnic entrepreneurs. The prominent characters are self-confidence, hard work, careful/economical calculations, independence, tenacity, contribution to the family, consistency, ingenuity, flexibility, and courage to face business challenges. The formation of entrepreneurial characteristics is determined by environmental factors of the entrepreneur, namely the family, school and community environment. Entrepreneurship is a creative and innovative process that involves the courage to take risks, the ability to see opportunities, and the spirit to create added value for oneself and society. An entrepreneur is not just selling or trading, but has a leadership spirit, strong motivation, and the ability to adapt and innovate in facing challenges. Values such as self-confidence, hard work, courage to take risks